Integrated Monetary and Exchange Rate Frameworks - Lúcio Vinhas de Souza (Tinbergen Institute, 2002)
Here the author empirically estimates if the different monetary and exchange rate frameworks observed in the Accession Countries of Central and Eastern Europe and the Baltics do yield different outcomes in terms of level and variance of a set of nominal and real variables. The author follows and extends the methodology developed by Kuttner and Posen (2001), who perform a combined analysis of the individual effects of exchange rate regimes, central bank independence and announced targets in nominal variables, for a large set of developed and developing countries, and estimate that a setup that combines a free float, an independent monetary authority and inflation targeting yields an outcome that mimics the price stabilization advantages of a hard peg without its drawbacks in terms of extreme volatility. This sample of countries, not covered by the Kuttner and Posen study, supports their conclusions, for both nominal and real variables, testing for both the individual and combined effects of the frameworks, indicating that a flexible exchange rate regime, coupled with a independent monetary authority and inflation targeting, would be Pareto-improving when compared to harder regimes.
Keywords: E5; P2; 330; monetary authority independence; inflation targeting; exchange rate regimes; EU enlargement.; Geldpolitik; Währungssystem; Wechselkurssystem; Vergleich; Osteuropa; Makroökonomischer Einfluss